2011
DOI: 10.2214/ajr.10.4687
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Peritoneal Dissemination: Comparison of 18F-FDG PET/CT, Diffusion-Weighted MRI, and Contrast-Enhanced MDCT

Abstract: PET/CT is the most useful technique for pathologic staging in the care of patients with malignant disease. If PET/CT is not available, DWI can be used as a screening tool.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
66
0
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(75 citation statements)
references
References 25 publications
5
66
0
4
Order By: Relevance
“…However, FDG-PET has given false-negative results for well-differentiated pulmonary adenocarcinoma (Higashi et al, 1998;Cheran et al, 2004), or small volumes of metabolically active tumor (Satoh et al, 2011), and false-positive results for inflammatory nodules (Goo et al, 2000;Nomori et al, 2004). In addition, FDG-PET is not widely available because of its high cost.…”
Section: Discussionmentioning
confidence: 99%
“…However, FDG-PET has given false-negative results for well-differentiated pulmonary adenocarcinoma (Higashi et al, 1998;Cheran et al, 2004), or small volumes of metabolically active tumor (Satoh et al, 2011), and false-positive results for inflammatory nodules (Goo et al, 2000;Nomori et al, 2004). In addition, FDG-PET is not widely available because of its high cost.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, combined morphologic and metabolic assessment provided by PET/CT yields superior diagnostic results compared to morphologic assessment by contrast-enhanced CT. The combination with other functional imaging modalities including diffusion and perfusion MR imaging as provided by PET/ MRI might result in further improvement of the diagnostic performance in the follow-up after HIPEC [14,16]. The combination of PET and dynamic contrast-enhanced MRI might contribute besides metabolic information also information regarding tissue perfusion which might be useful in the differentiation between malignant and inflammatory tissue [11].…”
Section: Discussionmentioning
confidence: 99%
“…The combination of PET and dynamic contrast-enhanced MRI might contribute besides metabolic information also information regarding tissue perfusion which might be useful in the differentiation between malignant and inflammatory tissue [11]. Diffusion-weighted magnetic resonance imaging could further enhance tissue characterization in patients with recurrent PC after HIPEC [16]. These options may contribute to further improvement in the follow-up period of patients with PC after HIPEC using PET/MRI to assess recurrent PC.…”
Section: Discussionmentioning
confidence: 99%
“…Cui et al (80) concluded that the detection rate of extrahepatic cholangiocarcinoma was significantly higher for DWI (94.3%) than for MRCP (74.3%), and the positive and negative predictive values of DWI (100%, 91.3%) were higher than those of MRCP (81.3%, 62.5%). Additionally, DWI was found to be a useful technique for screening peritoneal dissemination in a cohort of 107 patients with primary gastrointestinal or genitourinary tract malignancies (81).…”
Section: Abdominal Applicationsmentioning
confidence: 99%